2013
DOI: 10.1155/2013/149060
|View full text |Cite
|
Sign up to set email alerts
|

Axon Guidance Mechanisms for Establishment of Callosal Connections

Abstract: Numerous studies have investigated the formation of interhemispheric connections which are involved in high-ordered functions of the cerebral cortex in eutherian animals, including humans. The development of callosal axons, which transfer and integrate information between the right/left hemispheres and represent the most prominent commissural system, must be strictly regulated. From the beginning of their growth, until reaching their targets in the contralateral cortex, the callosal axons are guided mainly by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 77 publications
(88 reference statements)
1
19
0
Order By: Relevance
“…The observed reductions in interhemispheric connectivity in bipolar I disorder patients are consistent with previous reports of reduced integrity of the CC in bipolar disorder [Barysheva et al, 2013;Emsell et al, 2013;Lagopoulos et al, 2013;Leow et al, 2013;Sarrazin et al, 2014;Torgerson et al, 2013;Wang et al, 2008] and may be reflective of a decrease in the number, density, caliber, and/or myelination of callosal axons, with recent findings pointing more towards myelination than axon abnormalities [Lewandowski et al, 2014]. Around 200-250 million axons pass through the CC [Nishikimi et al, 2013;Paul et al, 2007] to connect primary, secondary, and higher-order cortices [Aboitiz et al, 2003]. Interhemispheric axons have widespread arbors that terminate in many regions besides the topographically equivalent one [Houzel and Milleret, 1999] and it has been suggested that these heterotopic projections may be important to propagate activity to other areas, thereby contributing to the formation of large-scale neuronal ensembles promoting diverse aspects of cortical processing [Varela et al, 2001].…”
Section: Discussionsupporting
confidence: 89%
“…The observed reductions in interhemispheric connectivity in bipolar I disorder patients are consistent with previous reports of reduced integrity of the CC in bipolar disorder [Barysheva et al, 2013;Emsell et al, 2013;Lagopoulos et al, 2013;Leow et al, 2013;Sarrazin et al, 2014;Torgerson et al, 2013;Wang et al, 2008] and may be reflective of a decrease in the number, density, caliber, and/or myelination of callosal axons, with recent findings pointing more towards myelination than axon abnormalities [Lewandowski et al, 2014]. Around 200-250 million axons pass through the CC [Nishikimi et al, 2013;Paul et al, 2007] to connect primary, secondary, and higher-order cortices [Aboitiz et al, 2003]. Interhemispheric axons have widespread arbors that terminate in many regions besides the topographically equivalent one [Houzel and Milleret, 1999] and it has been suggested that these heterotopic projections may be important to propagate activity to other areas, thereby contributing to the formation of large-scale neuronal ensembles promoting diverse aspects of cortical processing [Varela et al, 2001].…”
Section: Discussionsupporting
confidence: 89%
“…MicroRNA was recently discovered to serve as another level of regulators for these chemical cues and related signalling pathways (Chiu et al, 2014; Iyer et al., 2014). Axon guidance crossing CNS midline in developing spinal cord, the cortico-spinal tract (CST) and the corpus callosum is guided mainly by short-range cues derived from the midline structure and the neighbouring pioneer axons (Kaprielian et al, 2000; Nishikimi et al, 2013). …”
Section: Synaptogenesis and Neural Circuit Developmentmentioning
confidence: 99%
“…Callosal formation requires a cascade of dynamic events to be precisely coordinated spatially and temporally (Donahoo and Richards, 2009;Fame et al, 2011;Nishikimi et al, 2013). Callosal projection neurons mainly reside in cortical layers II and III and, to a lesser extent, layers V and VI.…”
Section: Introductionmentioning
confidence: 99%